Monitoring body composition and physical fitness of elite female basketball players after 16 weeks of in-season training - Franca, C.; Franca, A.; Marques, A.; Ihle, A.; Lopes, H.; Santos, F.; Gouveia, E. R. (Journal of Physical Education and Sport, 2022)
Understanding the physiological changes in playersf profiles during the season is crucial to optimize training prescription according to playersf needs towards a high-level game performance. The purpose of this study was to assess the variation in body composition and physical fitness of elite female basketball players after 16 weeks of inseason training. The sample was composed of 13 elite female basketball players aged 19.7 ± 4.3 years (height: 173.7 ± 9.8 cm, body mass: 70.4 ± 11.3 kg). Body composition, static strength, lower-body explosive strength, speed, agility, and aerobic endurance, were assessed initially (T1) and 16 weeks after the regular season (T2). Significant improvements were found between T1 and T2 for the squat jump (t = -2.433, p <= 0.05, d = -0.39), the 20 m linear sprint (t = 2.493, p <= 0.05, d = 0.87), and the Yo-Yo Intermittent Endurance Test-Level 2 (t = -3.746, p <= 0.01, d = -0.34). Lower-body explosive strength showed a significant contribution to agility and speed. The visceral fat area presented a greater negative correlation with the aerobic and anaerobic capacity. Sports practitioners and coaches should be aware of the importance of monitoring playersf body composition and physical fitness to assess the physiological responses to the training process and to optimize training prescription. Training contents may be adjusted according to the responses recorded to achieve the defined goals. The positive contribution of lower-body explosive strength to speed and agility, emphasizes the need to include in-season strength programs targeted to enhance players' overall physical fitness.